2014
DOI: 10.1007/s00221-014-4066-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of horizontally rotating sound on standing balance

Abstract: Postural control is known to be the result of the integration and processing of various sensory inputs by the central nervous system. Among the various afferent inputs, the role of auditory information in postural regulation has been addressed in relatively few studies, which led to conflicting results. The purpose of the present study was to investigate the influence of a rotating auditory stimulus, delivered by an immersive 3D sound spatialization system, on the standing posture of young subjects. The postur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
1
27
0
4
Order By: Relevance
“…This decrease in sway, while in line with results from other static sound studies, is slight compared to our previous rotating sound study, in which subjects reached a decrease in sway of about 30% (Gandemer et al, 2014). In the present experiment, even in the 3-source conditions, subjects still had less auditory information available than with rotating sound (no variation in acoustic cues, and only three discrete spatial positions for sound).…”
Section: Experiments 1: Building An Auditory Environmentsupporting
confidence: 92%
See 2 more Smart Citations
“…This decrease in sway, while in line with results from other static sound studies, is slight compared to our previous rotating sound study, in which subjects reached a decrease in sway of about 30% (Gandemer et al, 2014). In the present experiment, even in the 3-source conditions, subjects still had less auditory information available than with rotating sound (no variation in acoustic cues, and only three discrete spatial positions for sound).…”
Section: Experiments 1: Building An Auditory Environmentsupporting
confidence: 92%
“…Some researchers refer to an “auditory anchorage” effect (Deviterne et al, 2005), under the hypothesis that the spatial information provided by static sound sources can help subjects to construct a representation of the space surrounding them, and thus better stabilize. When we compare the results of our rotating sound study (Gandemer et al, 2014) (roughly 30% decrease in sway) to those of the static sound studies (roughly 10% decrease in sway), it is clear that moving sources (with the direction rather than the distance varying) lead to better stabilization. We assume that rotating sound provides more spatial information, as the acoustic cues vary and the source travels all around the subject.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Several studies have observed that external environmental sounds can act as a reference for controlling aspects of walking such as body posture and orientation (Karim et al, 2018) and can improve standing postural balance (Easton et al, 1998;Deviterne et al, 2005;Kanegaonkar and Amin, 2012;Gandemer et al, 2014;Rumalla et al, 2015;Horowitz et al, 2019). A considerable body of research has suggested that during walking, control of frontalplane motion requires greater involvement of the nervous system than sagittal-plane motions (MacKinnon and Winter, 1993;Bauby and Kuo, 2000;O'Connor and Kuo, 2009;McAndrew et al, 2010).…”
Section: Spatial Controlmentioning
confidence: 99%
“…Plus précisément, les mécanismes évolués du système de planification motrice lors de l'écoute, modulerait l'activité de systèmes plus primitifs comme les réflexes vestibulo-spinaux et la synchronisation sensori-motrice. Notons enfin que des études récentes soutiennent l'influence de la rythmique du son (vitesses de rotation sonore dans un système ambisonique) sur la stabilisation posturale en station debout [Gandemer 2014]. …”
Section: Système Vestibulaireunclassified